Kindergarten students' and their parents' perceptions of science environments: achievement and attitudes - Robinson, Esther (Curtin University, 2003)
This study explored the classroom learning environment in science among kindergarten students. In particular, I investigated both students' and their parents' perceptions of both preferred and actual learning environments. Additionally, I explored associations between student outcomes (achievement and attitudes toward science) and the nature of the classroom learning environment (as perceived by students and by their parents). The study involved the construction and validation of a learning environment questionnaire that was used by both parents and kindergarten students. Although the questionnaire was validated for use with five- and six-year-old kindergarten students, the same format was used for both parents and students. Prior learning environment studies (Fraser, 1998a) typically have involved the use of questionnaires neither by parents (with a notable exception being the recent study by Allen and Fraser, 2002) or by such young students. There is little doubt that, in just two decades, the field of classroom learning environment has progressed enormously (Fraser, 1998a) and that research involving qualitative methods and research involving quantitative methods each have made outstanding contributions to this overall progress (Tobin & Fraser, 1998). A historical look at the field of learning environments over the past few decades shows that a striking feature is the availability of a variety of economical, valid and widely applicable questionnaires for assessing student perceptions of classroom environments (Fraser, 1998b). This learning environment study is significant not only because it involves very young students (kindergarten) and their parents, but also a classroom learning environment questionnaire was developed and validated in Spanish, for both students and parents.The design of the study involved a sample of 172 kindergarteners from six classes and 78 parents of the same students from the same six classes. The ethnic make-up for this group of 172 students was 11.8% White, 49% Black, 33.6% Hispanic, and 5.6% of other nationalities. The gender breakdown was 40.4% boys and 59.6% girls. Approximately 45% of the kindergarten student population was made up of English Speakers of Other Languages (ESOL) students. The instruments used included modified versions in English and Spanish of the What Is Happening In This Class (WIHIC)? questionnaire and of the Test of Science-Related Attitudes (TOSRA). A major finding of the study was that the modified version of the What Is Happening In This Class? (WIHIC) questionnaire in the English and Spanish languages displayed satisfactory factorial validity and internal consistency reliability when used with kindergarten students and their parents. Secondly, parents perceived a more favorable actual classroom environment than did kindergarten students, but students preferred a much more favorable classroom environment than did their parents. The magnitudes of differences between students and parents are greater for the preferred form than the actual form. Finally, statistically significant associations were found between kindergarten students' perceptions of the. classroom environment and the outcomes of achievement and attitudes to science.